REPAYMENT POSITION OF LIABILITIES BERWEEN WORKER’S RIGHT AND TAX DEBT - Gita Ovanda Dwi Cahyaning Wahono; Thefany Bella Risadewi; Nabila Azilla Patty (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
In the matter of Bankruptcy, fulfillment of the right of the state within the matter of taxation is taking preference has been arranged under Law Number 16 of 2000 concerning General Provisions and the Procedures of Taxation as amended by Law Number 28 of 2007 and in accordance with Article 1137 of Civil Code. Referring from the provisions above, the right of the state to receive payment over the debt of taxation is a prioritized and the state is positioned as the preferred creditor. The Taxation Law gives a special treatment and higher position on which the tax debt is first to be paid by the debtor and followed by the right borne by the separatist creditor. On the other hand, Law Number 13 of 2003 concerning Employment also regulates that the fulfillment of the wages and other rights of the labor and positioned the labor as preferred creditor on which the privilege is given by the law. However, there are no statements in the Employment Law that stated the position of labor as a preferred creditor is higher than separatist creditor in the matter of bankrupt as what the Taxation Kaw expressed creditor is higher than the separatist creditor within the matter of tax payment. That distinction seems positioned the preferred creditor status of labor is lower than the position of separatist creditor on the matter of right fulfillment in bankruptcy. It is certainty that the statement which stated that the collection of tax debts has the right to preceded than other debts does not fit in this matter. Eventually, there is a decision of Constitutional Court Number 67/PUU-XI/2013 that provides a change within the position labor’s right on the matter of bankruptcy. Keywords: Repayment, Liabilities, Workers Rights, Tax Debt